PONDERAL AND REPRODUCTIVE PERFORMANCE DURING RAIN SEASON OF NELLORE PRIMIPAROUS HEIFERS PREVIOUSLY SUPPLEMENTED WITH PROTEIN IN DRY SEASON - Nogueira, Ana Paula Carneiro (2015)
The objective of this study was to evaluate, in rainy season, the effect of protein complementation during dry season on Nellore primiparous heifers. We used 39 primiparous heifers, with an average age of 24-36 months, reared on Brachiaria decumbens and Brachiaria Brizantha pasture, for 205 days. The animals were weighed every 28 days, after fasting for 12 hours. The experimental design was a split plot, the two treatments were distributed in two installments, the six periods in subplots and the animals were the replications. The following variables were analyzed: weight, hip height, body condition score, average daily weight gain and average monthly growth, presenting the respective values of 318.5 kg, 142 cm, 3.24, 0.580 kg and 2.55 cm respectively for previously supplemented animals, and 309.6 kg, 141 cm, 3.23, 0.584 and 2.29 kg cm for  non-supplemented animals. There were no significant differences between the two experimental groups. Pregnancy rate of supplemented animals was 57% and it did not differ from non-supplemented animals’ rate (45%). Calving rate was 100% for both groups. In the rainy season, after supplementation, heifers that did not receive supplementation during the dry period of the previous year had similar reproductive and weight performance as the supplemented ones.Keywords: beef cattle; dietary restriction; feedback; protein supplementation; reproduction.